Protection of Personal Data and Technology. In Search of the Lost Paradise - Travieso, Juan Antonio (Revista Tribuna Internacional, 2016)
IT technology triggers changes that influence the whole society, specially due to the globalization’s effect in the information flows, which presses to define a new concept of the privacy in a dramatic way. The main object here is not to point out new issues, but to find solutions to the dilemmas that pressure and change the society doing of each progress a real threat. Legislation constitute a part of the right approach, but the conflict takes place when the involved right contrasts with the technology. In such a context, it seems that there has been defined an area of lustful freedom with a subtle anonymity together with a mysterious amusement that the human person had lost.